Urban Upgrading and Ecosystem Conservation: The Kurt Beer Ecological Park Interpretation and Research Centre, Piura - Salazar Chirinos, Diego Renato; La Rosa Boggio, Diego Orlando; Torres Samillán, Rosa Amelia (LACCEI, 2025)
This article studies the sustainable architectural design proposal of an Ecosystem Interpretation and Research Center in the Kurt Beer Ecological Park in Piura, Peru. The main objective is to re-evaluate the dry tropical locust forest ecosystem, promote ecological research and establish sustainable tourism in a context saturated by uncontrolled urban sprawl, the loss of biodiversity and insufficient infrastructure at park level. A descriptive and systematic procedure was used, reaching the theoretical foundations and cases of interpretation centres and urban parks. The project presents sustainable architecture, sensory museography and community participation as a basis for design. Argues that the introduction of such infrastructure will not only improve the conservation of Piura’s natural heritage, but also provide an example for urban upgrading and sustainable development in comparable urban environments.